Laboratory Analysis Using Coconut Shell from Bekasi Regency for Drilling Mud Additives on Oil and Gas Wells - Hernowo Widodo; Mohammad Riyadi Setyarto; Andhy Andhy; Mohamad Prastya; Amaliah Annisa (Universitas Islam Riau (UIR) Press, 2020)
Drilling activity in deep formation usually gave greater challenges to the engineer due to its high pressure and temperature. To minimize this problem, drilling mud needs to be modified into a certain condition where it should be performed well in those extreme situations. The drilling mud quality does not significantly decrease, it simply requires better quality of mud at certain points at high temperatures. Certain additives are needed to maintain their performance. Therefore, this study aims to improve the quality of drilling mud by adding additives from carbon powder originating from coconut shells. Coconut shells are burned and processed until they become nanometer-sized, then used as additives in drilling mud. Then, several analyses such as XRD, SEM, as well as the rheology of drilling mud are evaluated. XRD analysis result shows the element from the coconut shell powder was graphite. Laboratory analysis results indicate that drilling mud with coconut shell powder provides better rheological value compared to the same drilling mud without the additives. It was observed that the mud with coconut shell powder performed better at high pressure.